Fixed bed dynamics of single and multicomponent adsorption of pentane and hexane isomers in ZIF-8 - Henrique, Adriano (2020)
Single, quinary and septenary fixed bed breakthrough experiments of pentane (nC5/iC5) and hexane (nC6/2MP/3MP/23DMB/22DMB) isomers were performed in shaped zeolitic imidazolate metal organic framework ZIF-8. Adsorption equilibrium isotherms for linear nC5 and nC6 were measured from the single component breakthrough curves covering the temperature range between 373 and 473 K and partial pressures up to 50 kPa. The equimolar septenary (nC5/iC5/nC6/2MP/3MP/23DMB/22DMB) and quinary (iC5/2MP/3MP/23DMB/22DMB) studies were performed at the same temperature range and total hydrocarbon pressure of 25 kPa. In the septenary experiments the following sorption hierarchy was observed: nC6 > nC5 > 2MP > 3MP > iC5 > 23DMB > 22DMB. Results also show that the sorption of the linear nC5 and nC6 is dominated by equilibrium in contrast with the sorption of branched isomers which is kinetically controlled. The quinary experiments with C5/C6 branched paraffins evidences the partially separation by classes of mono- and di-branched isomers. The equilibrium data were modelled by the Sips isotherm and the fitted parameters were used to simulate the breakthrough data through a mathematical model developed in a Matlab code using the method of lines (MOL). In the numerical simulations equal diffusivities constants (Dc/rc2) for linear nC5/nC6 were used, being it 0.002 s−1 at 373 K, which is a value 100 times higher than its respective value for the mono-branched isomers iC5, 2MP and 3MP, and 300 times higher than for the di-branched hexane isomer 22DMB. It is also shown the effect of the residence time of the gas regarding the fixed bed separation of the pentane and hexane isomers, from where it is clear that increasing the residence time improves the separation between the compounds.